Is Chayote Farming Profitable? A Financial Performance Analysis in Fakfak Regency - Arga Ramadhana; Rofina Kabes (Tarjih : Agribusiness Development Journal, 2026)
Chayote is one of the main sources of income for the majority of households in Kampung Mananmur, Kayauni District, Fakfak Regency. The village’s location, approximately one hour from the center of Fakfak City, poses a challenge for farmers, particularly those lacking personal transportation, in marketing their harvests. This study aims to analyze the production costs, revenue, and the economic feasibility of chayote farming using the Revenue–Cost (R/C) Ratio in Kayauni District, Fakfak Regency. The research employed a quantitative descriptive approach with a census (saturated sampling) technique, where all farmers in the population were included as respondents. A total of 33 farmers residing in Kampung Mananmur participated. Data were collected through structured questionnaires distributed uniformly to all respondents. The results indicate that the average annual revenue of chayote farming is IDR 22,267,002, while the average annual production cost is IDR 8,277,998. The economic feasibility analysis shows an R/C Ratio of 3.68, suggesting that chayote farming in Kayauni District is profitable and feasible for further development, as the ratio exceeds one.